Assessment of adverse drug reactions to antituberculosis regimen in a tertiary care hospital - Kuriachan, Sanitha; Krishnan, Prakash; Chogtu, Bharti; George, Manu Mathew (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Adverse drug reactions are common with multidrug therapy in tuberculosis, if detected early can improve patient compliance and prevent emergence of resistance. Methods: A prospective observational study as a part of Pharmacovigilance Program under Central Drugs Standard Control Organisation was conducted in Kasturba hospital, Manipal to collect adverse drug reactions (ADR). Data of patients reported with antitubercular treatment (ATT) related ADRs from September 2012 to August 2013 was evaluated for patient demography, type of tuberculosis, ATT regimen, organ/ system affected and time of onset of ADR. ADRs were then subjected to causality assessment as per WHO scale. Results: A total of 65 ADRs were reported in 60 patients during the study period, of which 46.7% were in males and 53.3% in females. 85% of ADRs were reported in patients with pulmonary tuberculosis. 77% of ADRs were observed with daily regimen. Common ADRs were hepatitis (40%), gastritis (15%), skin reactions (15%), peripheral neuropathy (14%), gout (6%) and nephritis (3%). Median duration for the onset of ADR was 31 days each for hepatitis, gout, nephritis and 20, 11, 9 days for gastritis, peripheral neuropathy and skin reactions respectively. As per causality assessment, 80% of ADRs were assigned “possible”, 11% “probable” and 9% “certain”. As per severity scale 27.7% of ADR were severe, 36.9% were moderate. Conclusions: Early detection and management of ADRs is vital for the success of ATT and patient adherence.